Aerobic decolorization, degradation and detoxification of azo dyes by a newly isolated salt-tolerant yeast Scheffersomyces spartinae TLHS-SF1. (March 2016) - Tan, Liang; He, Muyang; Song, Li; Fu, Xinmei; Shi, Shengnan
Highlights: Azo dye degradation and detoxification by salt-tolerant yeast was firstly studied. A salt-tolerant Scheffersomyces spartinae strain was isolated and identified. Various azo dyes could be decolorized by S . spartinae TLHS-SF1. Acid Scarlet 3R was mineralized and detoxified by S . spartinae TLHS-SF1. Abstract: Isolation, identification and characterization of a salt-tolerant yeast capable of degrading and detoxifying azo dyes were investigated in this study. Possible degradation pathway of Acid Scarlet 3R was proposed through analyzing metabolic intermediates using UV–Vis and HPLC-MS methods. Furthermore, the Microtox test was performed to evaluate the acute toxicity of the dye before and after biodegradation. The results showed that a salt-tolerant yeast named TLHS-SF1 was isolated and identified as Scheffersomyces spartinae basing on 26S rDNA analysis. The optimal decolorization and growth parameters were: sucrose 2 g L −1, (NH4 )2 SO4 0.6 g L −1, yeast extract 0.08 g L −1, NaCl ⩽ 30 g L −1, 160 r min −1, 30 °C and pH 5.0–6.0. More than 90% of 80 mg L −1 3R could be decolorized within 16 h under the optimal conditions. 3R was possibly degraded successively through azo-reduction, deamination and desulfonation pathways, and its acute toxicity obviously decreased by strain TLHS-SF1.